When do Refugees Return Home? Evidence from Syrian Displacement in Mashreq - Beaman, Lori (World Bank, Washington, DC, 2021)
This paper provides an empirical analysis of refugee returns to the Syrian Arab Republic. Since 2011, about 5.6 million Syrians—more than a quarter of the country’s pre-conflict population—have been registered as refugees. By mid-2018, only about 1.8 percent of them had returned to Syria voluntarily. This paper compiles a novel data set with administrative data for 2.16 million refugees, existing and new household surveys, a new conflict-events database, and nightlights data for Syria to analyze the correlates of these returns. A reduction in conflict intensity and an increase in luminosity in Syria strongly increase the likelihood of refugees’ return. Differential return rates are observed along key demographic characteristics, such as age, gender, and family status between high and low conflict intensity areas. Interestingly, improvements in the conditions faced by refugees in exile can also increase the likelihood of return.